2018
DOI: 10.1002/micr.30402
|View full text |Cite
|
Sign up to set email alerts
|

Distal nerve transfer from the median nerve lumbrical fibers to the distal ulnar nerve motor branches in the palm: An anatomical cadaveric study

Abstract: Background The aim of the current study is to investigate the first and second lumbrical nerves as potential fibers donors to the deep motor branch of the ulnar nerve to avoid intrinsic atrophy in high ulnar nerve injuries. Methods Sixteen fresh frozen cadaveric hands were dissected, the radial lumbrical nerves accessed, and a coaptation, either in reverse end‐to‐side or in double end‐to‐side through a bridge nerve graft, was created to the deep motor branch of ulnar nerve. Semithin sections were taken from sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(40 reference statements)
0
5
1
Order By: Relevance
“…Lumbrical muscle innervation occurred typically in the proximal to middle third junctions of the muscle. 23 In the current study, a dual innervation was solely observed for LM 2 , while Lauritzen and Szabo 18 observed LM dual innervation in 68% (of LM 3 in 64% and of LM 1 and LM 2 in 4%, per each). No dual innervation of LM 4 was observed in the current study.…”
Section: Lumbrical Nerve Entrance Point Variability In Lumbrical Musclecontrasting
confidence: 38%
“…Lumbrical muscle innervation occurred typically in the proximal to middle third junctions of the muscle. 23 In the current study, a dual innervation was solely observed for LM 2 , while Lauritzen and Szabo 18 observed LM dual innervation in 68% (of LM 3 in 64% and of LM 1 and LM 2 in 4%, per each). No dual innervation of LM 4 was observed in the current study.…”
Section: Lumbrical Nerve Entrance Point Variability In Lumbrical Musclecontrasting
confidence: 38%
“…In 2017, Colonna et al [36] suggested using the branch for the first lumbrical as a babysitter for the deep motor branch of the ulnar nerve to avoid intrinsic atrophy. This hypothesis was based on anatomical studies and qualitative and quantitative analysis of nerve fibers.…”
Section: Anterior Interosseous Nerve To Ulnar Motor Branch Transfer T...mentioning
confidence: 99%
“…3 A previous study demonstrated the microscopic feasibility of nerve coaptation of the motor branches of the first lumbrical muscles (LM) as donor nerve candidates to restore the function of adductor pollicis muscle (ADP) and to achieve a passing prehensile function. 4 The authors reported the results of a cadaveric study in 8 patients (5 men and 3 women) demonstrating different LM innervation patterns, in particular the relatively common presence of double branches innervation in 62.5% and dual innervation of the second lumbrical muscle (LM2) in 12.5%.…”
Section: Letter To the Editormentioning
confidence: 99%
“…A previous study demonstrated the microscopic feasibility of nerve coaptation of the motor branches of the first lumbrical muscles (LM) as donor nerve candidates to restore the function of adductor pollicis muscle (ADP) and to achieve a passing prehensile function. 4…”
mentioning
confidence: 99%